Relay sowing of lentil (Lens culinaris subsp culinaris) to intensify rice-based cropping - Malik, A.I.; Ali, M.O.; Zaman, M.S.; Flower, K.; Rahman, M.M.; Erskine, W. (Cambridge University Press, 2016)
The cropping systems of the Eastern Gangetic Plains of Bangladesh, India and Nepal are based on rice. There is a scope to intensify such systems through diversification with lentil, the most popular food legume. Two strategies were evaluated to fit lentil into the short fallow between successive monsoonal (i.e., T. aman) and pre-monsoonal (aus) or irrigated rice (boro) crop. These were early-flowering sole-cropped lentil and relay-sown lentil into rice. Firstly, 18 early-flowering lentil lines at three contrasting sowing dates were tested over two seasons on a research station at Ishurdi in Bangladesh. Secondly, relay sowing was evaluated at the same location with six early-flowering lines and two control cultivars in two seasons. It was also assessed on ten farms in Western Bangladesh, comparing relay with sole cropping over 3 years. Flowering in the early-flowering lentil lines was consistently 9–17 days earlier, than the control cultivars, but they did not achieve an economic yield (<1·0 t/ha). Relay sowing with an existing cultivar produced an economic yield of lentil, which was comparable or higher than sole-cropped lentil in all situations. The relay-sown lentil matured in sufficient time to allow the land to be prepared for the succeeding rain-fed rice crop. It was concluded that the substitution of relay-sown lentil for fallow in the monsoonal rice–fallow–rain-fed rice cropping pattern is a useful option to intensify and diversify cropping in the Eastern Gangetic Plain.